2021
DOI: 10.3390/pharmaceutics13111875
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Aspects of Nanocarriers for Smart Anticancer Therapy

Abstract: Drug delivery to tumor sites using nanotechnology has been demonstrated to overcome the drawbacks of conventional anticancer drugs. Altering the surface shape and geometry of nanocomposites alters their chemical properties, which can confer multiple attributes to nanocarriers for the treatment of cancer and their use as imaging agents for cancer diagnosis. However, heterogeneity and blood flow in human cancer limit the distribution of nanoparticles at the site of tumor tisues. For targeted delivery and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 148 publications
(163 reference statements)
0
2
0
Order By: Relevance
“…Acidity is a unique hallmark of the tumor microenvironment. Many pH-sensitive nanomedicines were designed and prepared to respond to the acidic tumor microenvironment promoting antitumor efficiency. Inorganic nanomaterials, which possess a diverse range of structure, composition, morphology, and physicochemical properties have been used in cancer treatment and diagnosis as delivery carriers. Recently, various metal oxides or calcium-based nanomaterials have been widely used as pH-sensitive inorganic nanomaterials. It has been reported that ZnO NPs could be used as pH-responsive drug carriers, which possess pH-triggered drug release characteristics displaying a response to acid and a rapid dissolution to Zn 2+ at pH <5.5, especially in lysosomes used for intracellular drug delivery platforms. The intracellular Zn 2+ produced by ZnO NPs has cytotoxic effects in tumor cells. , In addition, ZnO NPs could significantly induce the generation of ROS in tumor cells. In particular, ZnO NPs can make full utilization of disproportional reaction, Haber–Weiss reaction, or Fenton reaction to compensate for O 2 -depletion, thus greatly improving the therapeutic efficacy against hypoxic tumors . ZnO NPs also have good optical properties and high stability to be a promising candidate for bioimaging. , ZnO NPs could be used to in situ upconvert NIR to visible light through the second harmonic generation (SHG) mechanism for tumor imaging. , Recently, we designed an H 2 O 2 -triggered intelligent photodynamic therapy (PDT) nano delivery system, LCL/ZnO, that could selectively regulate the tumor-derived endothelial cells (TECs) and specifically kill tumor cells by producing different singlet oxygen ( 1 O 2 ) in response to different H 2 O 2 gradients in TECs and tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…Acidity is a unique hallmark of the tumor microenvironment. Many pH-sensitive nanomedicines were designed and prepared to respond to the acidic tumor microenvironment promoting antitumor efficiency. Inorganic nanomaterials, which possess a diverse range of structure, composition, morphology, and physicochemical properties have been used in cancer treatment and diagnosis as delivery carriers. Recently, various metal oxides or calcium-based nanomaterials have been widely used as pH-sensitive inorganic nanomaterials. It has been reported that ZnO NPs could be used as pH-responsive drug carriers, which possess pH-triggered drug release characteristics displaying a response to acid and a rapid dissolution to Zn 2+ at pH <5.5, especially in lysosomes used for intracellular drug delivery platforms. The intracellular Zn 2+ produced by ZnO NPs has cytotoxic effects in tumor cells. , In addition, ZnO NPs could significantly induce the generation of ROS in tumor cells. In particular, ZnO NPs can make full utilization of disproportional reaction, Haber–Weiss reaction, or Fenton reaction to compensate for O 2 -depletion, thus greatly improving the therapeutic efficacy against hypoxic tumors . ZnO NPs also have good optical properties and high stability to be a promising candidate for bioimaging. , ZnO NPs could be used to in situ upconvert NIR to visible light through the second harmonic generation (SHG) mechanism for tumor imaging. , Recently, we designed an H 2 O 2 -triggered intelligent photodynamic therapy (PDT) nano delivery system, LCL/ZnO, that could selectively regulate the tumor-derived endothelial cells (TECs) and specifically kill tumor cells by producing different singlet oxygen ( 1 O 2 ) in response to different H 2 O 2 gradients in TECs and tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“… 49 Then, environmental responsive intelligent nanocarriers have emerged, offering enhanced precision, selectivity, and sensitivity in delivering OVs. 50 Researchers developed a pH-responsive polymer-coated OA; this hybrid carrier demonstrated superior targeted action, improved cellular uptake, and anti-tumor efficacy under specific pH levels. 51 , 52 , 53 Additionally, external ultrasound further enhanced tumor tropism and penetration of viral nano-delivery platforms.…”
Section: Organic Npsmentioning
confidence: 99%